EXPLORING THE RELATIONSHIP BETWEEN PROCEDURAL JUSTICE AND INNOVATIVE WORK BEHAVIOR IN HOSPITALITY INDUSTRY - Noerchoidah Noerchoidah; Dhyah Harjanti (Jurnal Manajemen dan Kewirausahaan, 2019)
The purpose of this study is to examine the relationship between procedural justice, knowledge sharing and innovative work behavior. The research model and hypothesis were developed from related literature. The data was collected through survey method on 297 supervisors of four and five star hotels in East Java, Indonesia. The obtained data from the questionnaire were tested with Partial Least Square (PLS) to investigate the research model. The results confirm that procedural justice has positive impact on knowledge sharing. While the effect of knowledge sharing on innovative work behavior is another finding of this research. The implications of this study are discussed in the conclusions section of the study